51-38=8 and 44-38=8 are both equivalent
Answer:
3/2 and -4
Step-by-step explanation:
that is the answer
Step-by-step explanation:
3 - 2(b - 2) = 2 - 7b
To solve this first distribute -2 to (b - 2)
3 + (-2b + (-2) x -2) = 2 - 7b
when we simplify this it becomes:
3 + (-2b + 4) = 2 - 7b
We take (-2b + 4) out of the parenthesis:
3 - 2b + 4 = 2 - 7b
Now simplify again.
7 - 2b = 2 - 7b
Now send all the b's to one side and constants on the other.
7 - 2 = -7b +2b
5 = 5b
b = 1
Answer: 4x² + 4x - 2 - ![\frac{3}{2x+3}](https://tex.z-dn.net/?f=%5Cfrac%7B3%7D%7B2x%2B3%7D)
<u>Step-by-step explanation:</u>
You can use either synthetic or long division. I am using synthetic division:
2x + 3 = 0 ⇒ x = ![-\frac{3}{2}](https://tex.z-dn.net/?f=-%5Cfrac%7B3%7D%7B2%7D)
| 4 10 4 -6
<u>| ↓ -6 -6 3 </u>
4 4 -2 -3 ← <em>-3 is the remainder</em>
↓ ↓ ↓
4x² +4x -2 ← <em>factored polynomial</em>
Answer:
8 =g
Step-by-step explanation:
We have two points so we can use the slope formula
m = ( y2 -y1)/(x2-x1)
6 = ( g - -10)/(5-2)
6 = (g+10)/(5-2)
6 = (g+10)/3
Multiply each side by 3
6*3 = g+10
18 = g+10
Subtract 10
18-10 =g
8 =g